Lessons Learned From the First 10 Consecutive Cases of Intravenous Bacteriophage Therapy to Treat Multidrug-Resistant Bacterial Infections at a Single Center in the United States - Aslam, Saima; Lampley, Elizabeth; Wooten, Darcy; Karris, Maile; Benson, Constance; Strathdee, Steffanie; Schooley, Robert T (Open forum infectious diseases, 2020)
Abstract Background Due to increasing multidrug-resistant (MDR) infections, there is an interest in assessing the use of bacteriophage therapy (BT) as an antibiotic alternative. After the first successful case of intravenous BT to treat a systemic MDR infection at our institution in 2017, the Center for Innovative Phage Applications and Therapeutics (IPATH) was created at the University of California, San Diego, in June 2018. Methods We reviewed IPATH consult requests from June 1, 2018, to April 30, 2020, and reviewed the regulatory process of initiating BT on a compassionate basis in the United States. We also reviewed outcomes of the first 10 cases at our center treated with intravenous BT (from April 1, 2017, onwards). Results Among 785 BT requests to IPATH, BT was administered to 17 of 119 patients in whom it was recommended. One-third of requests were for Pseudomonas aeruginosa, Staphylococcus aureus, and Mycobacterium abscessus. Intravenous BT was safe with a successful outcome in 7/10 antibiotic-recalcitrant infections at our center (6 were before IPATH). BT may be safely self-administered by outpatients, used for infection suppression/prophylaxis, and combined successfully with antibiotics despite antibiotic resistance, and phage resistance may be overcome with new phage(s). Failure occurred in 2 cases despite in vitro phage susceptibility. Conclusions We demonstrate the safety and feasibility of intravenous BT for a variety of infections and discuss practical considerations that will be critical for informing future clinical trials. Bacteriophage therapy (BT) is an emerging therapeutic strategy against multidrug resistant infections. We demonstrate safety and successful outcome in 7/10 cases treated with intravenous BT and share lessons learned, BT referral pattern, and regulatory aspects in the US.